Activation Energy and High Temperature Oxidation Behavior of Multi‐Principal Element Alloy. Issue 11 (24th May 2017) - Grewal, Harpreet Singh; Sanjiv, Ramachandran Murali; Arora, Harpreet Singh; Kumar, Ram; Ayyagari, Aditya; Mukherjee, Sundeep; Singh, Harpreet
Abstract : Activation energy and diffusion kinetics are important in modulating the high temperature oxidation behavior of metals. Recently developed multi‐principal element alloys, also called high entropy alloys (HEAs), are promising candidate material for high temperature applications. However, the activation energies and diffusion kinetics of HEAs have been limitedly explored. We investigate the diffusional activation energy for oxidation of Al0.1 CoCrFeNi HEA. Compared to conventional steels and Ni‐based super alloys, the HEA showed a significantly higher diffusion activation energy. This behavior is explained based on low potential energy of the lattice and interstitial sites which effectively trap the atoms, limiting their diffusion. The atomic mean jump frequency for interstitial diffusion of oxygen in the HEA is four‐orders of magnitude lower than T22 and T91 steels and seven‐orders of magnitude lower compared to pure iron. Al0.1 CoCrFeNi HEA showed the lowest oxidation rate compared to conventionally used steels, super‐alloys, and coatings. Abstract : Al0.1 CoCrFeNi high entropy alloy shows significantly high activation energy and oxidation resistance. High activation energy lowers the mean jump rate of oxygen atom resulting in sluggish diffusion.